Integrating Backlight With Color-Filter-Free Panel for Enhancing Performance of LCD - Tun-Chien Teng; Chun-Hao Sun (IEEE Photonics Journal, 2020)
In this study, we proposed an innovative concept of integrating a polarized color-separating backlight with a color-filter-free LC panel for enhancing performance of the curved LCD system. We design a two-level folded backlight to exploit the light sources LEDs with color enhancement by quantum-dot technology to produce color beams emerging at separate angles with a linearly polarizing state. The integrated LC panel focuses the separating color beams onto the corresponding subpixels with no need of the color filter; redirects the color beams at respective angles into the normal and reforms their angular shapes to be identical for attaining good color uniformity in the viewing cone. We established a system model for simulation to evaluate its performance. According to the simulation results, it performs the high optical efficiency of 33.75% that is about four times the traditional LCD, and displays color gamut of 94.1% NTSC (CIE 1931). It also provides the illuminance uniformity of 90% above and good color uniformity in both the spatial space and angular space of the viewing cone with horizontal and vertical angular widths of 100o and 75o, respectively. Furthermore, the simulation results demonstrate that the design can apply to a 55-inch curved LCD and further extend the maximum diagonal size up to 88 inches while keeping slim volume with a minimal thickness of 6.5 mm.